1998
DOI: 10.2527/1998.761118x
|View full text |Cite
|
Sign up to set email alerts
|

Tribasic copper chloride and copper sulfate as copper sources for weanling pigs.

Abstract: We conducted three 28-d experiments involving a total of 915 pigs to assess the relative efficacy of tribasic Cu chloride (Cu2[OH]3Cl) and Cu sulfate pentahydrate (CuSO4.5H20) in diets for weanling pigs. Experiments 1 and 2 were conducted at an experiment station (University of Kentucky), and Exp. 3 was conducted at a commercial feed company's swine research facilities (United Feeds, Inc.). The basal diet was a fortified corn-soybean meal-dried whey diet (1.25% lysine) with no antimicrobials in Exp. 1 or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 11 publications
(21 reference statements)
7
57
1
1
Order By: Relevance
“…The use of copper in swine feed has also been repeatedly shown to have a positive effect in production performance (42,43) and zinc are considered two of the most widely researched alternatives to growth promotion antibiotics to enhance swine performance and maintain health (45). In the current study, we found a wide range in the levels of copper and zinc used in swine feed and concentrations often much higher than the NRC recommendations, as depicted in Table 2.…”
Section: Discussionmentioning
confidence: 67%
“…The use of copper in swine feed has also been repeatedly shown to have a positive effect in production performance (42,43) and zinc are considered two of the most widely researched alternatives to growth promotion antibiotics to enhance swine performance and maintain health (45). In the current study, we found a wide range in the levels of copper and zinc used in swine feed and concentrations often much higher than the NRC recommendations, as depicted in Table 2.…”
Section: Discussionmentioning
confidence: 67%
“…A publication describing three 28-day experiments involving a total of 915 weaned piglets to assess the relative efficacy of TBCC and copper sulphate was submitted (Cromwell et al, 1998).…”
Section: Weaned Pigletsmentioning
confidence: 99%
“…The inclusion of Cu to starter diets for weaning pigs is a common practice in swine industry. Cu is mostly used as copper sulfate but Cromwell et al (1998) showed similar efficacy in the case of tri-basic copper chloride. The growth-stimulating properties of dietary copper have been attributed to its antimicrobial action however, it was shown that also intravenous injection of copper to weanling piglets stimulate their growth (Zhou et al 2014).…”
mentioning
confidence: 99%